1959
DOI: 10.1111/j.1365-2621.1959.tb17316.x
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF LEVEL OF IRRADIATION, TEMPERATURE AND LENGTH OF STORAGE UPON THE LEVEL OF CERTAIN CHEMICAL COMPONENTS AND PANEL SCORES FOR PRECOOKED BEEF, PORK AND VEALa,b,c

Abstract: Irradiation of certain meat products produces characteristic objectionable flavors and odors. It has been assumed that the objectionable flavors are due to certain chemical changes, and a number of workers (2,3,6,8,13) have reported values for various chemical components both before and after irradiation. Recently it has been shown that the level of hydrogen sulfide, methyl mercaptan and carbonyls appear to be closely associated with the poor acceptability of irradiated beef, pork and veal (10). However, data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1961
1961
2002
2002

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Our results show that all sulfur compounds decreased during storage. Our results seems to be in agreement with earlier observations that storage of products after irradiation generally improves the odor of irradiated meats ( , ). It is not clear whether the decrease in sulfur compounds observed in the present study was due to leakage of volatile sulfur compounds from the vials or to their reaction with other components of cooked turkey breast.…”
Section: Resultssupporting
confidence: 94%
“…Our results show that all sulfur compounds decreased during storage. Our results seems to be in agreement with earlier observations that storage of products after irradiation generally improves the odor of irradiated meats ( , ). It is not clear whether the decrease in sulfur compounds observed in the present study was due to leakage of volatile sulfur compounds from the vials or to their reaction with other components of cooked turkey breast.…”
Section: Resultssupporting
confidence: 94%
“…Around the same time some low boiling point compounds (hydrogen sulfide, acetone, acetaldehyde, methyl mercaptan, etc.) were identified in cooked beef (Pearson et al, 1959;Kramlich and Pearson, 1960; Pippen and Nonaka, 1960).…”
Section: Review Heterocyclic Compounds Found In Cooked Meatsmentioning
confidence: 99%
“…They concluded that neither pre-nor post-irradiation storage influenced panel acceptance. In contrast, Pearson et al (1959) found post-irradiation storage of cooked meat resulted in an improvement in flavor, which is probably related to the differences between fresh raw and cooked meat, with heating being necessary to prevent further flavor deterioration caused by the indigenous enzymes during storage of raw irradiated meat. Merritt et al (1959) were able to identify 10 compounds in the volatiles isolated from irradiated beef using a low-temperature vacuum distillation procedure.…”
Section: Irradiation Flavor/odormentioning
confidence: 83%